Foraging responses of Antarctic fur seals to changes in the marine environment - McCafferty, DJ; Boyd, Ian Lamont; Walker, TR; Taylor, RI (1998)
This study examined the relative contribution of environmental variation and the seasonal demands of pup rearing on the foraging behaviour of female Antarctic fur seals Arctocephalus gazella at Bird Island, South Georgia (54 degrees S, 38 degrees W), during 3 austral summers (1994 to 1996). Time-depth recorders measured the diving behaviour of 72 individuals during a total of 385 foraging trips totalling 1964 d at sea. The frequencies of krill, fish and squid in the diet were estimated from prey items contained in seats. In 1996, a year of high krill abundance, females made shorter foraging trips, fewer dives and spent more time ashore than in 1994 when krill was scarce. Females fed exclusively on krill in 1996, and frequent shallow daytime diving indicated that krill were close to the surface during the day. In 1994 and 1995 deeper and longer-duration daytime dives were associated with a higher proportion of fish and squid in the diet. Foraging trip duration, ashore duration and dive frequency increased through the course of the 1995 and 1996 lactation seasons. Females, therefore, appeared to match pup demands by increasing both time feeding at sea and energy delivery to the pup on land. However, the importance of sea surface temperature and duration of night in multiple regression models suggested that physical factors were also important in explaining the seasonal pattern of fur seal foraging behaviour.